Onychopapilloma – a rare tumour of the nail apparatus - Sobjanek, Michał; Michajłowski, Igor; Pęksa, Rafał; Lakomy, Joanna; Nowicki, Roman (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction. Onychopapilloma is a very rare benign tumour of the nail matrix and nail bed. Clinically onychopapilloma presents as longitudinal erytronychia, exceptionally as leukonychia or melanonychia. After nail avulsion, circumscribed, keratinized cone-shaped structure is seen. In histopathology distal subungual hyperkeratosis and nail matrix metaplasia and papillomatosis are observed. Etiopathogenesis of onychopapilloma is unknown. Treatment is only surgically. Objective. Presentation of first Polish case of onychopapilloma. Case report. A 32 year-old healthy woman was admitted to our department due to subungual longitudianal tumour of the right thumb, presented as erytronychia. Lesion was excised. Histopathologic examination confirmed diagnosis of onychopapilloma. Conclusions . Onychopapilloma is a rare nail apparatus condition with uncharacteristic clinical feature. Tumour should be distinguish from inflammatory and neoplastic disorders.